Evolving Concepts of Reflux: The Ups and Downs of the LES - Tom R DeMeester (Canadian Journal of Gastroenterology)
The common denominator for virtually all episodes of gastroesophageal reflux in health and disease is the loss of the barrier that confines the gastric environment to the stomach. Factors important in the function of the barrier are its pressure, length and position. In early reflux disease, overeating, gastric distention, delayed emptying and aerophagia lead to transient losses of the barrier. A permanent loss results from inflammatory injury to the muscle of the barrier with free flow of gastric juice into the esophageal body and its subsequent injury. Corrective therapy requires augmentation or restoration of barrier function.